105 Digital transformation – what can we learn from the experiences and perceptions of young people, parents and hospital staff?. (23rd February 2023) - Sipanoun, Pippa; Wray, Jo; Gibson, Faith; Oulton, Kate
Abstract : Background: Implementing an electronic patient record (EPR) system with a tethered patient portal (MyGOSH) in a children's hospital was always going to be a challenge. The Going Digital study sought to understand the experiences and perceptions of all users of the new system before and after implementation. Methods: A concurrent mixed methods design was utilised over a three-year period consisting of: World Café workshops, pre/post implementation surveys and interviews, and a focus group. This approach enabled understanding of the breadth and depth of user experiences including the practical and ethical considerations related to digital transformation. Results: A total of 6245 participants took part in the study. Findings were complex and heterogeneous. Benefits from implementation were reported such as easier access to health information and improved communication from care teams, however, potential benefits were more readily described due to a prolonged period (12-18 months) for all users, particularly hospital staff, to adjust to using the new system. Young people ( n =488) wanted access to their health records, requiring support in doing this. Parents ( n =3955) perceived staff to be unprepared for the hospital's transition to EPR/MyGOSH, which lead to a lack of standardisation, with varied approaches to care reported, leading to unfulfilled expectations. Complex tensions also existed in relation to the parental role and responsibilities, and their child's developing autonomy. Hospital staff members ( n =1802) found assessing competence/capacity for portal access complex, and managing user expectations was challenging whilst trying to promote equitable care provision. Conclusion: Complexities exist in implementing EPR/patient portal in a children's hospital, whilst allowing young people access to their records, however, the Going Digital study provides a recent, modern example of how this can be achieved. Recommendations for clinical practice and future research are described for all users of the system.